Beyond the Pale: “Poesía Postpoética” in Agustín Fernández Mallo’s Joan Fontaine Odisea - W. Michael Mudrovic (Studies in 20th & 21st Century Literature, 2012)
In a recent article defining his concept of “poesía postpoética,” Agustín Fernández Mallo chides and challenges his contemporaries for being behind the times. While not completely eschewing more traditional techniques of intertextuality and imagery, Fernández Mallo does stress the need to incorporate scientific and mathematical imagery. His book-length poem, Joan Fontaine Odisea (mi deconstrucción) (2005), exemplifies his “poesía postpoética” in its use of allusions to high and popular culture, and scientific concepts, along different types of discourse, to disrupt the commonplace perception of a unified poetic voice. This article will focus on Joan Fontaine Odisea as a modern poetic sequence that includes paratextual elements, framing devices, and images such as Dirac’s Delta function in particular, to provide readers with some preliminary strategies for reading and appreciating this work and Fernández Mallo’s “poesía postpoética.” The theoretical basis will rely on the philosophy of Deleuze and Guattari and on a recent book by Elizabeth Grosz, Chaos, Territory, Art.
Keywords: Agustín Fernández Mallo; poesía postpoética; Joan Fontaine Odisea; modern poetry; poetry; poetic voice; mathematics